Broadening didactic resource of physics dictation - Ilya A. Teplitsky; Serhiy O. Semerikov (Science Education Quarterly)
It is well known that even excellent scientific and methodological presentation of educational material cannot yield high results without constant monitoring of course assimilation. There are many forms of assessment; one of them is physics dictation. Systematic and regular implementation of dictations, especially of various types, significantly expands the possibilities of this form of work. In accordance with the lesson structure and its educational objectives, we employ several types of dictations (lasting 5 to 25 minutes).